Extending the Technology Acceptance Model: A New Perspective on the Adoption of Blockchain Technology - Chih-Hung Chen (Human Behavior and Emerging Technologies)
While previous studies have investigated the factors influencing Internet adoption, the findings may not be transferable to explain blockchain technology (BCT) adoption, despite its similarities to the Internet. This study addresses this gap by developing an extended technology acceptance model (TAM) to investigate the factors influencing BCT adoption. The model consists of four key factors, including strategic management and social influence at the firm level, and individual innovation and self-efficacy at the individual level. Data were collected from 384 employees at Taiwan Stock Exchange companies, and structural equation modeling was utilized to test the hypotheses. Results reveal that strategic management and social influence at the firm level have a direct impact on BCT adoption, which is indirectly influenced by perceived usefulness. Subsequently, training and support provided by the firm can enhance individual innovation and self-efficacy, which has direct effects on BCT adoption at the individual level and is partially mediated by perceived ease of use.